(untitled) (Journal of Engineering, 2021)
A total of 48 experiments were conducted to investigate the impact of slit weir dimensions and locations on the maximum scour depth and scour area created upstream. The slit weir model was a 110 mm slit opening, and it was installed at the end of the working section in a laboratory flume. The flume was 10.0 m long, 30 cm wide, 30 cm deep, and almost middle. It includes a 2 m working section with a mobile bed with 110 mm in thickness. In the mobile bed, two types of nonuniform sand (with a geometric standard deviation of 1.58 and 1.6) were tested separately. The weir dimensions and location were changed with flow rates. Then dimensions of the slit weir were changed from 60 x 110 mm to 60 x 70 mm (width x height), while the location of the slit weir was changed from the center of the flume to its side. Finally, the flow rates were changed from 2.6 to 8 l/s. The maximum value of scour depth and scour area was recorded 72 mm and 32357 mm2 when the slit height, the flow rate, D50 of the movable bed were 110 mm, 8 l/s, 0.3 mm, respectively.